2016
DOI: 10.1186/s12913-016-1472-9
|View full text |Cite
|
Sign up to set email alerts
|

How efficient are referral hospitals in Uganda? A data envelopment analysis and tobit regression approach

Abstract: BackgroundHospitals represent a significant proportion of health expenditures in Uganda, accounting for about 26 % of total health expenditure. Improving the technical efficiency of hospitals in Uganda can result in large savings which can be devoted to expand access to services and improve quality of care. This paper explores the technical efficiency of referral hospitals in Uganda during the 2012/2013 financial year.MethodsThis was a cross sectional study using secondary data. Input and output data were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 30 publications
4
123
0
7
Order By: Relevance
“…Given that the range of relative productive efficiency scores calculated by the DEA model falls between 0 and 1, a Tobit and truncated regression model has traditionally been used to evaluate the factors affecting the productive efficiency [10,16]. However, Simar and Wilson argued that the use of a Tobit or truncated regression in a two-stage analysis is inappropriate based on two reasons: firstly, the productive efficiency scores estimated by DEA may be corrected with each other; thus, the results in the error term in these models are serially correlated and a standard inference is not valid.…”
Section: Stage Two: Bootstrapping Truncated Regressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that the range of relative productive efficiency scores calculated by the DEA model falls between 0 and 1, a Tobit and truncated regression model has traditionally been used to evaluate the factors affecting the productive efficiency [10,16]. However, Simar and Wilson argued that the use of a Tobit or truncated regression in a two-stage analysis is inappropriate based on two reasons: firstly, the productive efficiency scores estimated by DEA may be corrected with each other; thus, the results in the error term in these models are serially correlated and a standard inference is not valid.…”
Section: Stage Two: Bootstrapping Truncated Regressionmentioning
confidence: 99%
“…In the initial stage, we considered the number of open beds, the number of health workers, the total expenditure, the number of doctors, the number of nurses, the number of devices over 10,000 Chinese Yuan, the hospital area, the total fixed assets, the total service cost and the cost per visit as the input indicators based on previous studies [10,13,28]. The initial output variables selected included total revenue, income from medical services, the number of patient discharges, outpatient and emergency visits, the number of health examinations, average inpatient days and bed occupancy rate [10,16,29].…”
Section: Input and Output Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The focus of the study is on methodology rather than the result. Finally, Mujasi et al (2016) investigate referral hospitals in Uganda. The authors found a long run efficiency (CRS) of almost 80% and a short run technical efficiency (VRS) of more than 91%.…”
Section: Previous Studies Of Hospital Efficiency In African Countriesmentioning
confidence: 99%